Performance of different weed management treatments on heat use efficiency of chickpea crop (Cicer arietinum) under rainfed conditions of Jammu - GUPTA, VIKAS; SINGH, MAHENDER; KUMAR, JAI; KUMAR, ANIL; SINGH, B N (The Indian Journal of Agricultural Sciences, 2014)
An experiment was undertaken during rabi 2008-09 and 2009-10 at Agronomy Research Farm, PRSS, Samba, SKUAST-J to find out the heat use efficiency of chickpea (Cicer arietinum L.) crop with different weed control treatments, viz. T1: weedy check; T2: Hand-weeding (HW) at 25-30 and 50-55 DAS; T3: Quizalofop-ethyl 40 g/ha at 20 DAS; T4: Quizalofop-ethyl 40 g/ha at 30 DAS; T5: Quizalofop-ethyl 50 g/ha at 20 DAS; T6: Quizalofop-ethyl 50 g/ha at 30 DAS; T7: Imazethapyr 25 g/ha at 20 DAS; T8: Imazethapyr 25 g/ha at 30 DAS; T9: Imazethapyr 40 g/ha at 20 DAS; T10: Imazethapyr 40 g/ha at 30 DAS; T11: Chlorimuron ethyl 4 g/ha at 20 DAS and T12: Chlorimuron ethyl 4 g/ha at 30 DAS evaluated in randomized block design with three replications under rainfed situations. Chickpea is a thermo-sensitive winter season crop. Heat use efficiency was computed at one month interval after sowing. The results revealed that heat use efficiency was found maximum at 90 DAS in chickpea crop. The heat use efficiency was found highest under hand-weeding at 25-30 and 50-50 DAS, however, the lowest values were found when herbicide Chlorimuron was used @ 4 g/ha at 30 DAS. The dry matter and seed yield are significantly differed among different weed control treatments. The heat use efficiency was found linearly (R2 = 0.70) related with dry matter accumulation at different days after sowing. The grain yield and biological yield heat use efficiency was found 0.33 and 0.90 kg/ha Â°C/day, respectively. The dry matter was found to be directly related to seed yield of chickpea crop with R2 = 0.98.